Stable carbon and oxygen isotopes and element ratios of planktic foraminifer Globigerinoides ruber (white) from sediment core M78/1_181-3 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler (PANGAEA, 2025)
The Mississippi River discharge effectively shaped the dynamics of the Loop Current in the Gulf of Mexico during transient climates and interglacials, and reacted in response to changes in sea level and atmospheric circulation. We here provide proxydata records from piston core M78/1-181-3 PC. The ~12 m-long core was recovered from the Mississippi-Alabama shelf very close to and southeast of the recent Mississippi delta (29°00.00 extquotesingleN 88°20.00 extquotesingleW) from 804 m water depth during R/V Meteor Cruise M78/1 in 2009 (doi:10.2312/cr_m78_1). The proxyrecords cover the last ~42 kyrs at centennial resolution. Planktic stable oxygen (δ18O, extperthousand VPDB) and carbon isotope analyses (δ13C; extperthousand VPDB) as well as elemental analyses were performed on the shallow-dwelling foraminiferal species Globigerinoides ruber (white). Sampling and analytical studies were carried out from 3 cm to 1220 cm core depth at ~5 cm spatial resolution. The stable isotope analyses were run on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV Carbonate Preparation Device at GEOMAR according to standard procedures (c.f. Nürnberg et al., 2008). The element/Ca ratios (Mg/Ca, Sr/Ca, Al/Ca, Fe/Ca, Mn/Ca) were determined on a VARIAN ICP-OES according to Nürnberg et al. (2008). The proxy data provide information on the surface water temperature and salinity development.